2003
DOI: 10.1598/rrq.38.2.4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the factors affecting reading performance of functionally illiterate adults and children matched by reading level

Abstract: S We examined the relations among phonological awareness, short‐term memory, orthographic ability, contextual information, and reading skill in a study of 60 functionally illiterate adults enrolled in Adult Basic Education programs. Using a multiple regression analysis, the results indicated that phonological awareness, orthographic ability, and context each accounted for a unique portion of the variance in reading skill. To compare the relative strengths and weaknesses of these adult readers to children, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
75
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 30 publications
14
75
2
2
Order By: Relevance
“…Past research has shown that skilled readers often fail to show a processing time difference between the correct homophone and the incorrect homophone conditions (Rayner et al, 1998), which suggests that skilled readers are using phonological codes to activate word meanings. The results from Greenberg et al (2002) and Thompkins and Binder (2003) suggest ABE readers may not be as proficient with using phonological representations compared to orthographic representations. If this is the case, the ABE adults may notice the incorrect homophone and slow down in that condition compared to when the correct homophone was present.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Past research has shown that skilled readers often fail to show a processing time difference between the correct homophone and the incorrect homophone conditions (Rayner et al, 1998), which suggests that skilled readers are using phonological codes to activate word meanings. The results from Greenberg et al (2002) and Thompkins and Binder (2003) suggest ABE readers may not be as proficient with using phonological representations compared to orthographic representations. If this is the case, the ABE adults may notice the incorrect homophone and slow down in that condition compared to when the correct homophone was present.…”
Section: Introductionmentioning
confidence: 91%
“…They concluded that phonological awareness is related to reading skill in adults as well as children. Thompkins and Binder (2003) examined relationships among phonological awareness, memory abilities, orthographic abilities, use of context, and reading skill in adults enrolled in ABE classes and children who were match to the adults on reading achievement level. They found that adults outperformed children in memory ability, use of context and orthographic abilities, while children outperformed adults on phonological awareness tasks.…”
Section: Introductionmentioning
confidence: 99%
“…However, they do not differ from the children on a nonspeech tone manipulation tasks (Pratt & Brady, 1988). Using a regression analysis, Thompkins and Binder (2003) found that phonological awareness accounted for a unique portion of the variance in A-IL reading scores. Functional illiteracy could therefore be viewed as an instance of developmental dyslexia that has gone untreated in childhood (Greenberg et al, 1997).…”
Section: The Phonological Deficitmentioning
confidence: 74%
“…Adult literacy students scored much lower than 1st-5th-grade children matched for reading level on word segmentation tasks, especially when segmenting into phonemes (Greenberg et al, 1997;Thompkins & Binder, 2003). However, they do not differ from the children on a nonspeech tone manipulation tasks (Pratt & Brady, 1988).…”
Section: The Phonological Deficitmentioning
confidence: 79%
“…En revanche, ils manipulent sans difficultés particulières des sons non linguistiques (Pratt & Brady, 1988). D'après une analyse de la régression menée par Thompkins et Binder (2003), les compétences métaphonologiques rendraient compte d'une part spécifique de la variance des scores en lecture des adultes illettrés. L'illettrisme pourrait donc être un cas particulier de dyslexie développementale qui n'aurait pas été prise en charge durant l'enfance (Delahaie et al, 2000;Greenberg et al, 1997).…”
unclassified